MENINGKATKAN HASIL BELAJAR PKn MELALUI PENERAPAN METODE TANYA JAWAB DENGAN FARIASI MEDIA PEMBELAJARAN PADA POKOK BAHASAN MASYARAKAT MADANI DI KELAS XI IPS1 SMA NEGERI 10 PEKANBARU: (Improving PKn Subject Result of the Capital Method trough Questions and Answer by Using Learning Variative Media on the Topic of the Community Society in Class XI IPS1 SMA Negeri 10 Pekanbaru) - Darmali, Darmali (Perspektif Pendidikan dan Keguruan, 2017)
This research is based on the low percentage of achievement on the Minimum Exhaustiveness Criteria that was given by the students of grade XI 1 SOCIAL 10 SENIOR HIGH SCHOOL Pekanbaru, school year 2015/2016 From the number of students 42 people who took the post test on the teaching materials Characteristic of civil society with Cooperative learning model, only 15 people can be passed (36.%) and the rest about 27 people are declared not graduated (64,%). The data indicate that the learning outcomes in these teaching materials can be declared unfinished. The disagreement is evident from the proof of the percentage of all students graduation only reached 36,%. The percentage is far from the ideal percentage between 80% - 100%. Even the percentage of graduation is smaller than the percentage of nongraduation. Therefore, for such cases it is necessary to hold a classical remedial. The process of classical remedial in this case the author did through classroom action research activities.